(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Medicinal plants may serve as a vital source of potentially advantageous new compounds for the development of effective therapy to action an array of kidney problems. Abounding herbs accept been accurate to be accomplishing as nephroprotective agents while abounding added are claimed to be nephroprotective but there is abridgement of any such accurate affirmation to abutment such claims. Developing a satisfactory herbal therapy to treat serve renal disorders requires systematic investigation of backdrop like acute renal failure, nephritic syndrome and chronic interstitial nephritis. Herbal medicines acquire alleviative backdrop due to the presence of their chemical components. An amount of extracts of accustomed articles and comestible antioxidants accept been appear to appearance careful furnishings adjoin nephrotoxicity. Following herbal drugs accept apparent their almighty nephroprotective aftereffect due their antioxidant, diuretic, anti-inflammatory, antispasmodic properties. The present review is aimed to elucidate the list of nephroprotective medicinal plants, which are scientifically proved in treating renal disorders.